2016
DOI: 10.4184/asj.2016.10.6.1042
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia at 4 Days Postoperatively Is the Most Significant Laboratory Marker for Early Detection of Surgical Site Infection Following Posterior Lumbar Instrumentation Surgery

Abstract: Study DesignCase control study.PurposeTo identify the most significant laboratory marker for early detection of surgical site infection (SSI) using multiple logistic regression analysis.Overview of LiteratureSSI is a serious complication of spinal instrumentation surgery. Early diagnosis and treatment are crucial.MethodsWe retrospectively reviewed the laboratory data of patients who underwent posterior lumbar instrumentation surgery for degenerative spinal disease from January 2003 to December 2014. Six labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Blood Hb levels partially reflect the nutritional status of patients (22,23). Furthermore, when the immunity of a patient is weakened, LYM is decreased and the patient becomes prone to infections, inhibiting wound healing (24).…”
Section: Discussionmentioning
confidence: 99%
“…Blood Hb levels partially reflect the nutritional status of patients (22,23). Furthermore, when the immunity of a patient is weakened, LYM is decreased and the patient becomes prone to infections, inhibiting wound healing (24).…”
Section: Discussionmentioning
confidence: 99%
“…CT, MRI, PET) because these methods are very expensive and requires a lot of time [13][14][15] . Therefore, postoperative laboratory markers are often used to screen SSI due to their objectivity, low cost and convenience 12,16 .…”
Section: Discussionmentioning
confidence: 99%
“…After that, More and more scholars make a profound study at this field. Iwata et al showed that the lymphocyte count of <1,000/µL at 4 days postoperatively was the sole significant independent laboratory marker for early detection of SSI 16. Chao-Jun Shen et al reported 22 that neutrophil/lymphocyte count ratio (NLR)at 4 and 7days post-operation are valuable laboratory predictors for SSI in patients with posterior lumbar spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative C-reactive protein (CRP) level was significantly higher in patients with than without SSI [median (interquartile range), 0.5 (0.09-0.63) vs. 0.03 (0.02-0.15) mg/dL, respectively; P = 0.026]. The immunological parameters such as the neutrophil count, lymphocyte count, and N/L ratio were not different between patients with and without SSI immediately after the end of anesthesia although an elevated N/L ratio is reportedly correlated with the incidence of SSI after posterior lumbar instrumentation surgery [2]. Similarly, the plasma CRP level on both POD 7 and POD 14 but not POD1 was significantly higher in patients with than without SSI [POD 1 4.41 (1.77-6.24) vs. 4.11 (2.46-5.61) mg/dL, respectively, P = 0.979; POD 7 3.55 (2.82-11.68) vs. 1.56 (0.84-2.62) mg/dL, respectively, P < 0.01; and POD 14 7.29 (1.14-9.74) vs. 0.31 (0.14-0.90) mg/dL, respectively, P < 0.01].…”
mentioning
confidence: 90%